Explicit analytical shape function calculation for macro-element in glue connection. Issue 27 (14th December 2022) - Santi, Gian Maria; Francia, Daniela; Cesari, Francesco
Abstract: This manuscript presents a simplified approach to adhesive joints calculation. Aviation and space rocket engineering constructions joints deals with coaxial cylindrical pipes that can be connected by adhesive with advantages in terms of tightness, aerodynamic efficiency, manufacturability, low weight. Glue joints are, therefore, considered and simplified in this article by the analytical calculation of the shape functions for a macro-element applied to the Volkersen's theory. The mathematical solution makes possible to calculate the explicit form of the stiffness matrix of the macro-element. The analysis proposed shows the perfect matching of the solution for a single element under classical mechanical loads.